Qual a resposta para essas contas?
(x/3 - 2/4)³=
(0,5 - 2x)³=
PS.: Resolver com o cubo da diferença
Respostas
respondido por:
1
respondido por:
1
a) (x/3 - 2/4)³ = (x/3)³ - 3.(x/3)².2/4 + 3.x/3.(2/4)² - (2/4)³
= x³/27 - 3.(x²/9).2/4 + 4.x/16 - 8/64
= x³/27 - x²/6 + x/4 - 1/8
b) (0,5 - 2x)³ = (0,5)³ - 3.(0,5)².2x + 3.0,5.(2x)² - (2x)³
= 0,125 - 3.0,25.2x + 1,5.4x² - 8.x³
= 0,125 - 1,5.x + 6.x²- 8.x³
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás